Penerapan Roll Bending Machine pada IKM Logam di Desa Tlahab Kecamatan Kledung Kabupaten Temanggung - R Arri Widyanto; Saifudin Saifudin (Celebes Abdimas: Jurnal Pengabdian Kepada Masyarakat, 2020)
Abstract. This Community Partnership Program is in partnership with BINA USAHA Small and Medium Industries which is engaged in the metal welding industry. BINA USAHA also produces equipment and simple machines for industrial processing of agricultural products from surrounding communities, such as tobacco chopper machines and coffee peeler. The production equipment owned by the partners is still conventional. This condition causes low production capacity, in addition, the existing equipment is less ergonomic, so it often creates work inconvenience for employees. Apart from low production capacity, the use of conventional equipment will also result in poor product quality, because the uniformity of the dimensions of the workmanship cannot be maintained. Meanwhile, problems in the field of management, product marketing are still limited to certain areas. This is due to the lack of information received by partners in finding areas for product marketing, lack of marketing networks and the marketing area is not yet extensive. This activity uses a participatory community empowerment model / Participatory Rural Appraisal so that it requires active participation from partners. The solutions offered to solve the problems faced by partners in this PKM scheme community service activities are: a). Equipment development, b). Production process training, c). Develop a marketing model. The output target to be achieved from this activity is the application of science and technology ROLLS BENDING MACHINE at IKM BINA USAHA, so as to increase the competitiveness of IKM products and improve the welfare of the community.